I-DISTANCE AND SEPARABILITY COEFFICIENT IN BUSINESS EVALUATION OF SMES IN AGRIBUSINESS - Popović, Blaženka; Ceranić, Slobodan; Paunović, Tamara (Economics of Agriculture, 2016)
Systematic and continuous process of measuring and comparing business results of companies regarding to business results of leaders, in order to obtain information that will help the company to take action to improve its performance, is in a function of improving business operations. Accordingly, the frst objective of this paper is, based on the coeffcient of separability, to determine which indicators of business conditions and business results have the greatest impact on differences in the business operations of the observed SMEs operating in the food industry. The second objective of this work is to make the ranking of companies based on the business conditions and business results using discriminant analysis (I-distance), and then, to determine the overall rank of companies using general ranking coeffcient (Ker). The results show that companies are signifcantly separated according to business results rather than to business conditions, and in addition, the business results also had a crucial impact on the overall rank of each company.